2008
DOI: 10.1002/ajpa.20790
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation in ancient Egyptians: A new technique based on anatomical reconstruction of stature

Abstract: Trotter and Gleser's (Trotter and Gleser: Am J Phys Anthropol 10 (1952) 469-514; Trotter and Gleser: Am J Phys Anthropol 16 (1958) 79-123) long bone formulae for US Blacks or derivations thereof (Robins and Shute: Hum Evol 1 (1986) 313-324) have been previously used to estimate the stature of ancient Egyptians. However, limb length to stature proportions differ between human populations; consequently, the most accurate mathematical stature estimates will be obtained when the population being examined is as sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 76 publications
3
72
0
2
Order By: Relevance
“…As expected, equations derived from lower limb bones perform better than those derived from upper limb bones based on r and SEE values, but the upper limb equations can be useful where lower limb bones are not preserved. SEEs are comparable with those of other studies using similar methods (e.g., Auerbach and Ruff, 2010;Béguelin, 2011;Raxter et al, 2008;Vercellotti et al, 2009).…”
Section: Sample-specific (Andean) Stature Estimation Equationssupporting
confidence: 84%
See 2 more Smart Citations
“…As expected, equations derived from lower limb bones perform better than those derived from upper limb bones based on r and SEE values, but the upper limb equations can be useful where lower limb bones are not preserved. SEEs are comparable with those of other studies using similar methods (e.g., Auerbach and Ruff, 2010;Béguelin, 2011;Raxter et al, 2008;Vercellotti et al, 2009).…”
Section: Sample-specific (Andean) Stature Estimation Equationssupporting
confidence: 84%
“…This broad range of equations was selected to explore the accuracy of previously published stature estimates for Andean skeletal samples (which have been based on Genovés, 1967or Trotter, 1970, 1958, 1977, and to explore the potential applicability of reportedly universal equations (Feldesman and Fountain, 1996) or those from hypothetically more morphologically similar New World groups. Analyses focused on equations using lower limb bone measurements, because these bones show a closer relationship to stature than upper limb bones as they form a direct component of final stature (Auerbach and Ruff, 2010;Raxter et al, 2008;. The ''Mexican'' equations of Trotter (1970) were not used because they are available for males only.…”
Section: Stature Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Zakrzewski, 2003(Zakrzewski, , 2007Pfeiffer and Sealy, 2006;Stynder et al, 2007;Giannecchini and Moggi-Cecchi, 2008;Ginter, 2008). Recent research relating to stature and body mass estimation in various skeletal populations (e.g., Auerbach and Ruff, 2004;Raxter et al, 2006Raxter et al, , 2008Giannecchini and Moggi-Cecchi, 2007;Smith, 2007;Ruff, 2007;Scuilli and Blatt, 2008) emphasizes the importance of these variables to anthropologists in archaeological and forensic contexts.…”
mentioning
confidence: 97%
“…The examination revealed that Shepespuptah was around 173 cm tall (Raxter et al 2008) and lived until 35-50 years of age. His skeletal remains show numerous pathological changes, which undoubtedly complicated his life (for the report in Czech, see Havelková 2013: 49-50).…”
Section: The Burial Of Shepespuptahmentioning
confidence: 99%